The modern movement in architecture: roots and expressions of formal language - Krastiņš, Jānis (Landscape Architecture and Art, 2025)
Studies its roots and reveals hitherto lesser-known examples of the style, analyses the development of the style in different countries and in Latvia, and compares the quality of different implementations of its formal language in different stages of history. Special attention is paid to different early examples that paved the way for the later development of the style. The historical place of the Modern Movement in the cultural heritage has been assessed. All images in the text are photographs by the author if not indicated otherwise.